(untitled) (Research, Society and Development, 2021)
The Atlantic Forest Biome is essential for 72% of the Brazilian population, but only a small part of the population has knowledge and values this environmental heritage. This biome is under constant threat; thus, strategies and actions are needed for its preservation and conservation. The Embu-Verde Environmental Preservation Area (EPA) concentrates a big part of the remaining biodiversity of the Atlantic Forest, and because it is close to the largest urban center in the country, it is increasingly threatened. The use of plants as a medicinal tool has been explored since the beginning of mankind. In fact, many of the compounds used in the health area derive from the flora. In this context, this study aimed to identify the medicinal potential of the EPA Embu-Verde flora, from the perspective that it is necessary to know to be able to preserve. Based on previous studies registering the biodiversity of EPA Embu-Verde, all the species of flora listed were investigated to identify its medicinal potential. We show here that of the 202 native species identified in the EPA Embu-Verde, there are 35 species of 23 botanical families that presented medicinal potential. The Myrtaceae family was the most cited, and its anti-inflammatory potential was the most prominent, moreover, several other uses were reported for the remaining flora. The medicinal potential of the flora of EPA Embu-Verde is still underestimated, therefore the recognition of medicinal species by the population is important. The preservation of the flora is essential to guarantee the possibility of future bioprospecting studies that will investigate the therapeutic potential of the still unknown medicinal species.